Revitalisasi Tembang Dolanan Terhadap Penguatan Pendidikan Karakter dan Penerapannya di SD Negeri Batursari 06 Mranggen - Wita Ermayanti; Ari Widyaningrum; Mira Azizah (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study was to describe the revitalization of the dolanan song towards strengthening the character education of students at SD Negeri Batursari 06 Mranggen and to describe the application of character values in the dolanan song at SD Negeri Batursari 06 Mranggen. This research method uses qualitative research methods. Data collection techniques come from observation, interviews, and questionnaires. The results of the analysis and discussion of the data obtained show that 1) the revitalization of the dolanan song towards the strengthening of character education at SD Negeri Batursari 06 has carried out revitalization with representation activities, by presenting dolanan songs through youtube and powerpoint media. (2) the application of character values in the dolanan song at SD Negeri Batursari 06 Mranggen has reached the moderate criteria in understanding the character values contained in the song dolanan Jaranan and Gundul-Gundul Pacul. Through the learning of the dolanan song, it is hoped that children will grow into cultured human beings, have good manners, have high character, have strong character, and are able to think critically, so that they are sensitive to social problems around them.